Migrating techniques, multiplying diagnoses: the contribution of Argentina and Brazil to early 'detection policy' in cervical cancer Técnicas que migram, diagnósticos que se multiplicam: a contribuição de Argentina e Brasil para a política de 'detecção precoce' do câncer cervical - Yolanda Eraso (História, Ciências, Saúde: Manguinhos)
This article on the early detection of cervical cancer focuses on the development of two leading diagnostic techniques - colposcopy and the Pap smear test - and their histories in Argentina and Brazil. It explores how diagnostic tools were transferred between Europe and the Americas, while examining the intersection of cultural and medical aspects and the processes of adaptation and resignification in the receiving countries. Colposcopy received little attention in the main Western medical centers until South American countries reasserted its significance in the 1950s. 'Peripheral' centers played a central role in early detection policies and the combined uses of these methods gave rise to a new stage of 'cumulative confidence' in cervical cancer diagnosis and screening. Este artigo trata da detecção precoce do câncer cervical. Coloca em evidência as duas principais técnicas diagnósticas, a colposcopia e o teste de Papanicolau, e mostra suas trajetórias no Brasil e na Argentina. Analisa o modo como se deu a transferência de métodos diagnósticos entre a Europa e as Américas, procurando perceber a interseção de aspectos médicos e culturais e ainda os processos de adaptação e ressignificação nos países que acolheram as novas técnicas. A colposcopia recebeu pouca atenção nos principais centros médicos ocidentais até os países sul-americanos validarem sua importância nos anos 1950. Centros 'periféricos' desempenharam papel crucial nas políticas de detecção precoce, e o uso combinado desses métodos deu lugar a novo estádio de 'confiança cumulativa' no exame e diagnóstico do câncer cervical.